2014
DOI: 10.1016/j.juro.2013.11.104
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Parastomal Hernia in Patients Undergoing Radical Cystectomy and Ileal Conduit Diversion

Abstract: We demonstrated that parastomal hernia will develop in nearly a third of patients after radical cystectomy with ileal conduit diversion. Prior laparotomy and severe obesity are independent risk factors. Preoperative counseling and preventative measures regarding parastomal hernia formation should be emphasized, particularly in these at risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 24 publications
2
56
2
Order By: Relevance
“…Studies investigating the frequencies of PSH after ileal conduit without a prophylactic mesh have reported rates between 0 and 29% [4][5][6][7][8][9][10][11]. The reported frequencies appear to have increased over the past 40 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies investigating the frequencies of PSH after ileal conduit without a prophylactic mesh have reported rates between 0 and 29% [4][5][6][7][8][9][10][11]. The reported frequencies appear to have increased over the past 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…The use of computed tomography (CT) scan examinations has also been proposed to have increased the reported incidence of PSH in other types of ostomies [25]. However, only one study has consistently examined all patients with a CT scan when detecting PSH after an ileal conduit [4]. Recent studies on PSH after colostomies have Data are shown as mean ± SD or n (%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If non-operative management is pursued in these patients, the risk of incarceration and requiring emergency surgery is increased at an estimated 2-3%/year (Table 1). [11][12][13][14][15][16] Nationally, the rate of emergency ventral hernia repair increased from 16.0% to 19.2% per 100,000 person-years in 2001 and 2010, respectively (p-value <0.05). 17 Outcomes of emergency surgery are dismal with increased risk of all complications including reoperation (RR 2.72, 95% CI 1.5-4.94), 30-day readmission (RR 1.61, 95% CI 1.23-2.11), and mortality (RR 13.1, 95% CI 6.39-26.86).…”
Section: Introductionmentioning
confidence: 99%